2019
DOI: 10.1007/s00167-019-05697-8
|View full text |Cite|
|
Sign up to set email alerts
|

Arthroscopic primary repair of proximal anterior cruciate ligament tears seems safe but higher level of evidence is needed: a systematic review and meta-analysis of recent literature

Abstract: Purpose To assess the outcomes of the various techniques of primary repair of proximal anterior cruciate ligament (ACL) tears in the recent literature using a systematic review with meta-analysis. Methods PRISMA guidelines were followed. All studies reporting outcomes of arthroscopic primary repair of proximal ACL tears using primary repair, repair with static (suture) augmentation and dynamic augmentation between January 2014 and July 2019 in PubMed, Embase and Cochrane were identified and included. Primary o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
93
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 80 publications
(98 citation statements)
references
References 83 publications
(150 reference statements)
2
93
2
1
Order By: Relevance
“…However, note that this review included some long-term follow-up studies from the nonselective open repair days, likely limiting the applicability of their conclusions. Regardless, both studies stressed the obvious lack of long-term studies on the modern technique of arthroscopic ACL repair [9,31]. It is felt that it is early in the resurgence of interest in ACL primary repair and that, as indications and techniques evolve, our understanding and outcomes will improve proportionately.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, note that this review included some long-term follow-up studies from the nonselective open repair days, likely limiting the applicability of their conclusions. Regardless, both studies stressed the obvious lack of long-term studies on the modern technique of arthroscopic ACL repair [9,31]. It is felt that it is early in the resurgence of interest in ACL primary repair and that, as indications and techniques evolve, our understanding and outcomes will improve proportionately.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, taking advantage of modern arthroscopic surgical techniques, materials, and devices, there has been a renewed interest in primary repair of ACL. In the last several years, some studies on ACL repair have shown good to excellent results with a failure rate ranging from 7% to 15% of cases [9][10][11][12][13]. Most articles recommend surgery within 4 weeks from injury; however, there is a wide variety of delay until treatment, including at least one case report of a patient treated 11 years after injury [14].…”
Section: Introductionmentioning
confidence: 99%
“…Historically, high failure rates of primary repair of both cruciate and collateral ligaments have been reported [21][22][23]. With increased awareness of the importance of patient selection by only performing repairs on proximal or distal type tears that can be reapproximated to their insertion, and the recent developments of additional suture augmentation, which is thought to protect the repaired ligament during rehabilitation, better outcomes of primary repair have been reported [24][25][26][27]. However, concern remains regarding this procedure as high failure rates of anterior cruciate ligament (ACL) repair have been reported among adolescents [28], while much less is known regarding posterior cruciate ligament (PCL) repair as the literature is scarce [29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…Returning to recently published literature on ACL repair, we notice that reported results are highly conflicting, with acceptable outcomes ranging from 40% to up to 90%. [ 17 20 ]. This great variability could be explained by the great variety of indications, surgical techniques, materials, and rehabilitation protocols.…”
mentioning
confidence: 99%